INTERNSHIP, SOCIAL VALUATION, AND SELF-EFFICACY AS DRIVERS OF ENTREPRENEURIAL INTENTION AMONG VOCATIONAL STUDENTS: A STRUCTURAL MODEL APPROACH - Lydiawati Soelaiman; Keni Keni; Fajri Adrianto; Tay Lee Chin (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
High unemployment among Indonesian Vocational High School (VHS) graduates highlights a persistent gap between school-acquired competencies and labour market demands. To address this, fostering entrepreneurial intention during early education is essential. This study research expands the entrepreneurial intention framework to the vocational education context in Indonesia, where empirical evidence on the psychological and contextual factors influencing entrepreneurial intention among VHS students remains limited. Specifically, the study examines how internship experience and social valuation influence entrepreneurial intention, with self-efficacy as a mediating variable and entrepreneur education support as a moderating variable. Employing a quantitative design, data were obtained from 160 VHS students in DKI Jakarta who had completed internship programs. The analysis usedPartial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS 4.0. The results show that internship experience and social valuation both increase self-efficacy, which has a strong effect on entrepreneurial intention. While internship experience does not directly lead to entrepreneurial intention, it influences it indirectly through selfefficacy. Social valuation affects entrepreneurial intention both directly and indirectly. The study also finds that entrepreneurial education support strengthens the effect of social valuation on entrepreneurial intention, but not the effect of internship experience or self-efficacy. The findings underscore the significance of social support and practical experience as essential components of entrepreneurial learning in vocational education to strengthen entrepreneurial intention among students.